Evaluation of researchers : a life cycle analysis of German academic economists - Michael Rauber; Heinrich W. Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2006)
In this paper we ague that any meaningful bibliometric evaluation of researchers needs to take into account that research productivity follows distinct life cycles. Using an encompassing data set portraying the research behavior of German academic economists, we first show that research productivity crucially depends on career age and vintage. Based on the identified effects, we develop a simple formula that shows how a researcher's performance compares to that of his or her peers. This kind of information may serve as an input for performance-related remuneration and track-record based allocation of research grants. We then go on to investigate the persistence of individual productivity. The Persistence issue is of special importance in the academic labor market because of the irrevocable nature of tenure. Finally, we show how life cycle considerations can be used in evaluations of university departments in order to render the resulting rankings insensitive to the age structure of the evaluated faculties.
Keywords: A14; A11; M51; J41; J24; 330; research productivity; performance evaluation; life cycles; rankings; Wirtschaftsforschung; Wirtschaftswissenschaftler; Erwerbsverlauf; Publikationsanalyse; Personalbeurteilung; Hochschule; Bewertung; Deutschland